Slow release of urea encapsulated by starch PVA matrix - Lum, Yip Hing; Shaaban, Azizah; Mohamad, Noraiham; Dimin @ Mohd Amin, Mohd Fairuz (Trans Tech Publications Ltd, 2016)
The hydrophobicity of starch/PVA blend was improved by crosslinking with boric acid.It was found that the swelling ratio of the boric acid modified starch/PVA matrix decreased as function of boric acid concentration. FTIR spectra and SEM images demonstrated that the urea had been encapsulated in polymer matrix successfully.The urea release characteristic was explained with respect to the swelling ratio and crosslinking density of polymer matrix.In addition,the matrix displayed a good barrier for controlling the release rate of urea from pellet.